Effect of Chronologic Age on Induction of Cystathionine Synthase, Uroporphyrinogen I Synthase, and Glucose-6-phosphate Dehydrogenase Activities in Lymphocytes - Gartler, Stanley M.; Hornung, Sigrid K.; Motulsky, Arno G. (Proceedings of the National Academy of Sciences - PNAS, 1981)
The activities of cystathionine synthase [L-serine hydro-lyase (adding homocysteine), EC 4.2.1.22], uroporphyrinogen I synthase [porphobilinogen ammonia-lyase (polymerizing), EC 4.3.1.8], and glucose-6-phosphate dehydrogenase (D-glucose-6-phosphate: NADP+1-oxidoreductase, EC 1.1.1.49) have been measured in phytohemagglutinin-stimulated lymphocytes of young and old human subjects. A significant decrease in activity with age was observed for cystathionine synthase and uroporphyrinogen I synthase but not for glucose-6-phosphate dehydrogenase. These changes could not be related to declining phytohemagglutinin response with aging. Age-related decreases in activity of some enzymes may be relevant for an understanding of the biology of aging. False assignment of heterozygosity, and even homozygosity, for certain genetic disorders, such as homocystinuria, may result when low enzyme levels are detected in the lymphocytes of older people.